2013
DOI: 10.1371/journal.pone.0062010
|View full text |Cite
|
Sign up to set email alerts
|

An International Comparison of the Effect of Policy Shifts to Organ Donation following Cardiocirculatory Death (DCD) on Donation Rates after Brain Death (DBD) and Transplantation Rates

Abstract: During the past decade an increasing number of countries have adopted policies that emphasize donation after cardiocirculatory death (DCD) in an attempt to address the widening gap between the demand for transplantable organs and the availability of organs from donation after brain death (DBD) donors. In order to examine how these policy shifts have affected overall deceased organ donor (DD) and DBD rates, we analyzed deceased donation rates from 82 countries from 2000–2010. On average, overall DD, DBD and DCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 18 publications
1
40
1
1
Order By: Relevance
“…We concede that this study is observational in nature and that we cannot ascribe causality to the changes observed. Nonetheless, we believe that these results show that overall NDD activity did not suffer from the introduction of a DCD program (in contrast to other reports in the literature 7,8,12 ). It is unlikely (given historical rates) that growth in NDD donation would have matched or exceeded that of DCD.…”
Section: Limitationscontrasting
confidence: 63%
See 1 more Smart Citation
“…We concede that this study is observational in nature and that we cannot ascribe causality to the changes observed. Nonetheless, we believe that these results show that overall NDD activity did not suffer from the introduction of a DCD program (in contrast to other reports in the literature 7,8,12 ). It is unlikely (given historical rates) that growth in NDD donation would have matched or exceeded that of DCD.…”
Section: Limitationscontrasting
confidence: 63%
“…Initially reported for kidney recipients, successful transplants from DCD donors have now been performed with lung, liver and, most recently, heart. [6][7][8][9][10] In the setting of this advance in organ donation, concerns have been raised about the quality and yield of organs from DCD and about whether an active DCD program replaces organs that would otherwise have been procured through NDD donation.…”
mentioning
confidence: 99%
“…Recent publications point to a trend toward increased numbers of DCD donors. [14][15][16] Advances in the last decade in trauma care and neurosurgical and neuroradiological interventions immediately after brain injury may result in improved initial survival of patients. As a result, patients who are to become organ donors are increasingly not meeting brain death criteria.…”
mentioning
confidence: 99%
“…International studies suggest that, due to a greater risk of damage to the organs during a cardiocirculatory death, there are 1.5 fewer transplanted organs per cardiocirculatory death donor than per brain death donor, as well as a higher risk of complications for some types of organs. 27 However, for kidneys-the organs in greatest demand in Canada-long-term outcomes for transplant patients are comparable for organs retrieved from both cardiocirculatory and brain death donors. 25,28,29 Early results are also promising for lung and liver transplants from DCD.…”
Section: Back To the Future: Donation After Cardiocirculatory Deathmentioning
confidence: 99%